Sosialisasi dan Penyuluhan Hukum Pengelolaan Hutan Berbasis Kearifan Lokal Di Kabupaten Aceh Utara - Yulia, Yulia; Herinawati, Herinawati (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
The forest management based on deep local wisdom has existed in the history of the Aceh community since the reign of Sultan Iskandar Muda. That is by applying the Forest Customary Law through the Forest Pawang Customary Institution. This Customary institution has a very important and strategic role in educating and inviting forest communities to be involved in forest management based on local wisdom. This service activity aims to increase understanding with village apparatus and traditional institutions in forest management based on local wisdom. This service is carried out through socialization and legal counseling in North Aceh District, namely: Sawang, Nisam, Langkahan, Pirak Timu, Paya Bakong and Geuredong Pasee sub-districts, because these districts still have high forest intensity. The results of this activity have provided an understanding for gampong apparatus and customary institutions in forest management and built an intensive communication network between village apparatus, traditional institutions and the district leadership meeting so that they can work together in protecting and conserving the forest. It is recommended to the village apparatus and customary institutions to immediately form the Forest Pawang Customary Institution and Village Qanun regarding forest management.